Restoration of the hip geometry after two-stage exchange with intermediate resection arthroplasty for periprosthetic joint infection - Hubert, Jan (Sci Rep, 2021)
Two-stage exchange with intermediate resection arthroplasty (RA) is a well-established surgical procedure in the treatment of chronic periprosthetic joint infection (PJI), whereby a higher failure rate of final hip geometry restoration due to tissue contraction is controversially discussed. The aim was to evaluate radiographic changes of hip geometry parameters during PJI treatment and to determine the impact of the intermediate RA on the final joint restoration after reimplantation of a total hip arthroplasty (reTHA). Radiographic parameters (leg length (LL), femoral offset (FO), horizontal/vertical acetabular center of rotation distance (h/vCORD)) of 47 patients (mean age: 64.1 years) were measured on standard radiographs of the pelvis and compared between four different stages during PJI treatment (pre-replacement status (preTHA), primary total hip arthroplasty (pTHA), RA and reTHA). The RA duration (mean: 10.9 months) and the number of reoperations during this period (mean: n = 2.0) as well as their impact on hip geometry restoration were evaluated. Between preTHA and pTHA/reTHA an equivalent restoration was measured regarding the FO (p < 0.001/p < 0.001) and hCORD (p = 0.016/p < 0.001), but not regarding the LL and vCORD. In contrast, analysis revealed no influence of RA and an equivalent reconstruction of LL (p = 0.003), FO (p < 0.001), v/hCORD (p = 0.039/p = 0.035) at reTHA compared to pTHA. Furthermore, RA duration (p = 0.053) and the number of reoperations after RA (p = 0.134) had no impact on radiographic hip geometry restoration. The two-stage exchange with intermediate RA does not alter the preexisting hip joint parameters, whereby a good restoration of the final hip geometry, independent of the duration or the number of reoperations, can be achieved.